Strategies for the formation of reading comprehension in teaching of the language (Primary, Secondary, Superior) - Alexandra Lisíchkina (Ибероамериканские тетради)
The article is concerned with the importance of the using of texts in the process of studying of foreign languages. The article gives an analysis of exercises for the texts. Attention is given to the differences between the exercises we use in the Russian and in the Spanish education systems.